Pengaruh Temperatur terhadap Jumlah Produk Hidrorengkah Fraksi Aspalten dari Aspal Buton dengan Katalis Mo-Ni/γ-Alumina - Rahmad Nuryanto; Wega Trisunaryanti; M. Utoro Yahya (Jurnal Kimia Sains dan Aplikasi, 2009)
Hydrocracking process of Butonian asphalt derived asphaltene using Mo-Ni/γ-alumina catalyst has been investigated. The processes were carried out in 1L stainless steel autoclave reactor. The reaction temperatures were 250, 300, 350 and 400C, initial pressure was 10 atm and catalyst/feed ratio was 1/2. The asphaltene was a pentane insoluble-benzene soluble (PI-BS) fraction of Butonian asphalt.The results of hydrocracking processes showed the conversion by means of 100% - coke (wt %) was followed equation konversi % (w/w) = 0,306 t (C) - 41,29Key words: hydrocracking, asphaltene, Mo-Ni/γ-alumina catalyst